Quality of life and neurological disability in children and young people with ataxia telangiectasia. (September 2022) - McGlashan, Hannah L.; Blanchard, Caroline V.; Luscombe, Celia; Prasad, Manish; Chow, Gabriel; Auer, Dorothee P.; Whitehouse, William P.; Dineen, Rob A.
Abstract: Aim: To explore neurological factors affecting quality of life (QoL) in children and young people with ataxia-telangiectasia (A-T), from both child and parent perspective. Method: 24 children/young people with A-T (mean age 11.2 ± 3.5 years; 13 males) and 20 parents were recruited, and 58% were reassessed after an average interval of 3.4 years. Participants completed the PedsQL QoL assessment. Participants with A-T underwent structured neurological examination. QoL data from 20 healthy controls and their parents was used for comparison. Results: Children/young people with A-T rated their QoL higher than parental ratings across time points, with no longitudinal change. Higher age of the child participant correlated with lower parental ( r = −0.43, p = .008) but not child ratings of QoL ( r = −0.16, p = .380). Child and parent QoL ratings from the A-T group were lower than respective ratings from controls ( η p 2 = 0.44 and η p 2 = 0.75 respectively, both p < .0005, controlled for socioeconomic status). Parental, but not child, ratings of QoL was predicted by a regression model based on neurological scores ( R 2 = 0.44, p =<.001). Interpretation: Neurological disability does not determine child/young person QoL ratings in A-T. While certain aspects of neurological disability predict parent-proxy ratings, there is no decline in QoL over time. These results may reflect resilience in the face of a complex life-limiting disorder. Graphical abstract: Image 1 Highlights: Child ratings of QoL in A-T are significantly higher than parental ratings. Age negatively correlated with parent QoL ratings, but there was no relationship between age and child QoL self-ratings. Neurological function significantly predicts parental, but not the child's own ratings of their QoL. Over time, QoL ratings did not decline with increasing disability reflecting high levels of resilience in this sample.